Diffusion tensor cardiovascular magnetic resonance. - Khalique,Z; Pennell,D (Postgraduate Medical Journal, 2019)
Cardiac structure and function are complex and inter-related. Current in vivo techniques assess the heart on a macroscopic scale, but a novel technique called diffusion tensor cardiovascular magnetic resonance (DT-CMR) can now assess the cardiac microstructure non-invasively. It provides information on the helical arrangement of cardiomyocytes that drives torsion and offers dynamic assessment of the sheetlets (aggregated cardiomyocytes) that rotate through the cardiac cycle to facilitate wall thickening. Through diffusion biomarkers, the expansion and organisation of the underlying myocardium can be described. DT-CMR has already identified novel microstructural abnormalities in cardiomyopathy, and ischaemic and congenital heart disease. This new knowledge supports the potential of DT-CMR to improve diagnostics and prognostication in various cardiac diseases.